Nucleotide sequence and conserved features of the 5.8 S rRNA coding region of Neurospora crassa. - Selker, E (Nucleic Acids Res, 1979)
The nucleotide sequence of Neurospora crassa 5.8 S rDNA and adjacent regions has been determined. The deduced 5.8 S rRNA sequence of Neurospora differs from the 5.8 S rRNA sequence of Saccharomyces cerevisiae at 13 of 158 residues. Nine of these differences are clustered in a segment capable of forming a short hairpin secondary structure thought to be involved in the 28 S - 5.8 S rRNA complex. These differences occur in pairs such that the potential secondary structure is preserved.